Trump 2.0: Unpacking the Potential Economic Impacts on OIC Countries - Riadhus Shufa Al Khairi; Muhammad Ali Mustofa (Muslim Business and Economics Review, 2025)
United States (US) President Donald Trump's trade policies during his first term were characterized by protectionist measures, including tariff increases and trade disputes with major economies. Following his re-election in 2024, similar policies are resurfacing and impacting global trade dynamics. This paper analyzes the potential economic consequences of Trump's second presidential term on Organisation of Islamic Cooperation (OIC) member countries, focusing on three key components: (1) a tariff on steel and aluminum, (2) a trade war with China, and (3) geopolitical tensions with BRICS nations. A Global Trade Analysis Project (GTAP) model is employed to simulate the short-run effects of these policies on gross domestic product, trade balance, and welfare in OIC countries. The results suggest that increased tariffs and trade conflicts may lead to shifts in global trade patterns, with potential negative spillover effects on OIC countries, particularly those with strong trade ties to the US, China, and BRICS member states. Trade diversion effects are also observed, indicating possible shifts in export flows. The findings provide insights into how OIC nations might navigate the uncertainties of a renewed Trump administration's economic policies.